2021
DOI: 10.1111/1467-8268.12505
|View full text |Cite
|
Sign up to set email alerts
|

HIV/AIDS and child malnutrition in eastern and southern Africa

Abstract: HIV/AIDS and child malnutrition are pervasive in eastern and southern Africa. This paper employs crosscountry panel data on 20 countries from 1991 to 2017 to explore the macro-level relationship between HIV/AIDS and child malnutrition. Using instrumental variables (IV) regression, we find that HIV/ AIDS is a robust predictor of long-term and chronic malnutrition. Conditional on various controls, the results demonstrate a positive empirical association between HIV/AIDS and stunting. Moreover, increased access t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…Thus, high HIV/AIDS prevalence and better nutritional outcomes can coexist under better socioeconomic conditions. While this scenario does not suggest that higher HIV/AIDS prevalence is causally associated with better nutritional outcomes, it reinforces the need to control for the underlying socioeconomic conditions in examining the association between HIV/AIDS prevalence and nutritional outcomes [35]. In Uganda, the UNICEF country report on the status of children reported that HIV/AIDS is one of the predominant common factors among parents of malnourished children [36].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, high HIV/AIDS prevalence and better nutritional outcomes can coexist under better socioeconomic conditions. While this scenario does not suggest that higher HIV/AIDS prevalence is causally associated with better nutritional outcomes, it reinforces the need to control for the underlying socioeconomic conditions in examining the association between HIV/AIDS prevalence and nutritional outcomes [35]. In Uganda, the UNICEF country report on the status of children reported that HIV/AIDS is one of the predominant common factors among parents of malnourished children [36].…”
Section: Introductionmentioning
confidence: 99%
“…National governments, development agencies and non‐governmental organizations are also committed to reducing, and ultimately eradicating, poverty in all its forms and dimensions (United Nations, 2017). According to the International Food Policy Research Institute (2015), this global commitment ensures healthy lives and promotes well‐being for all (Adika, 2021).…”
Section: Introductionmentioning
confidence: 99%